G559(P) Paediatric 'RECALL' Tool in Action: A strategy for Improving Paediatric Patient Safety in a Structured Way. (27th April 2016) - Green, K; Briscoe, A; Norrish, G; Wood, K; Runnacles, J
Abstract : Context: This safety improvement project took place in a district general paediatric department that sees 17, 000 children annually in A&E, with approximately 1000 admissions; around 60 of these requiring high dependency (HDU) care. This project focused on identifying areas for improvement in the care of this sickest group of patients. Problem: Children who deteriorate on the ward requiring HDU care are, by definition, the sickest children, and so analysis of their care is essential to identify missed opportunities to prevent deterioration and reduce morbidity. We identified a need for a formal pathway to identify areas for improvement and to subsequently disseminate learning to clinical staff. Assessment of problem and analysis of its causes: To review the care of all children who deteriorated on the ward requiring HDU care (or transfer out to PICU) we used an adapted version of the RECALL (Rapid Evaluation Cardio-respiratory Arrest with Lessons for Learning) tool. This provides a structured template to review the medical and nursing notes and identify areas for improvement. It focuses on assessment (recording of paediatric early warning score (PEWS)), escalation in response to deterioration, clinical reviews at appropriate points, interventions implemented and additional information (staffing levels, parental concerns). 37 children required HDU care in the six-month study period. The RECALL tool highlighted areas of good practice in care including accurate use of the Paediatric Early Warning Score (PEWS), and appropriate management plans acted on in a timely manner. However, it also identified areas for improvement, for example, children scoring 3 on PEWS not reported to nurse In charge or doctors, a discordance between nursing documentation and the clinical situation, and delayed medical reviews. Intervention: The issues identified in the analysis were recurring themes and similar missed opportunities were identified more than once. To disseminate these lessons and also feedback areas of good practice we created a paediatric risk newsletter to be distributed regularly across the medical and nursing teams. We also commenced monthly "safety meetings" to discuss lessons learnt from the previous month. Study design: This study was a retrospective analysis of the HDU data using the "RECALL structured template. Strategy for change: A monthly safety newsletter incorporating the results of the RECALL analysis is disseminated electronically via secure email as well as in paper form to help us reach all staff. The newsletter allows rapid dissemination of learning. Furthermore, the monthly safety meetings have been valuable to ensure the safety lessons learnt remain at the forefront and encourages staff to remain involved with contributing to patient safety. Measurement of improvement: The RECALL tool is being continually used to analyse patient care, allowing us to identify recurring themes that need to be addressed and measure the effect of changes made. These are reviewed regularly at risk meetings and displayed on a new safety noticeboard on the ward. Effects of changes: Using the RECALL tool has resulted in measurable improvements. wHowever, new themes are continually identified, highlighting the need for continual vigilance and intervention to improve patient safety. Lessons learnt: The RECALL tool is useful to identify improvements required in patient care, however a strategy is required to disseminate these lessons to frontline staff and engage them in continual improvement. A newsletter is a useful way of disseminating information to staff, however we have learnt that on its own it is not sufficient. We are therefore integrating a weekly learning point into the daily morning safety huddles and basing simulation scenarios on recent clinical cases. Message for others: Quick prospective analysis of patients' care using the RECALL tool is a simple way to identify missed opportunities to prevent deterioration. When recurring themes are identified staff education is critical to improve care. A newsletter is an efficient way of disseminating information.